Effectiveness of Yoga as an Adjunctive Therapy in Migraine: A Narrative Review - Fitas, Alicja; Dercz, Maciej; Głaszczka, Michał; Jabłońska, Urszula; Papciak, Kinga; Woźniak, Klaudia; Radliński, Michał; Palacz, Jakub; Korowaj, Karolina; Gardzielik, Aleksandra (Quality in Sport, 2026)
Background: Migraine remains a challenging neurological disorder, affecting millions worldwide and often disrupting daily life. While medications are still the first-line therapy, many patients struggle with side effects or end up discontinuing treatment. Consequently, there is a growing interest in complementary, non-pharmacological approaches, particularly mind-body practices such as yoga. Objective: In this narrative review, we explore what recent research reveals about adding yoga to standard migraine care. We focus on whether yoga can help with key clinical outcomes. Material and Methods: This narrative review evaluates the effectiveness of yoga therapy in migraine management, based on a comprehensive literature search of PubMed and Scopus (2007–2026). Included studies-primarily randomized controlled trials and meta-analyses assessed yoga’s clinical and physiological impacts on headache frequency, pain severity, disability and autonomic balance. Results: Integrating yoga into standard medical care appears to significantly reduce the frequency, duration and severity of migraine attacks. Regular practice may also minimize migraine-related disability and help restore autonomic nervous system (ANS) balance. Conclusions: Current evidence suggests that yoga is a safe and cost-effective adjunctive therapy for migraines. It significantly reduces headache frequency, pain intensity and attack duration, while simultaneously mitigating disability, restoring autonomic balance and enhancing patients' overall quality of life.